Application of iron–carbon microbial galvanic activated sludge combined with MBR process in the treatment of wastewater from comprehensive railway station - Zhang, Qi; Liang, Zheng; Guan, Xiaotao; Liang, Jingwen; Gao, Pan (Frontiers in Environmental Science, 2022)
The combined wastewater treatment application of iron-carbon micro-electrolytic activated sludge was carried out in MBR processor to treat the wastewater of Integrated railway station. The results show that the removal rates of COD, TN and TP of the original MBR processor are increased from 80%, 30% and 10% to 92%, 93.5% and 92%, respectively. Further research proves that the combined sewage treatment system has strong impact resistance when the concentration of COD, TN and TP changes greatly. In the in-depth analysis of the reaction process and reaction rate of the combined sewage treatment system, it is clear that the combined system is dominated by COD removal with high nitrogen removal efficiency of the sewage treatment system. The removal rate constants of various pollutants are as follows: KCOD (0.647±0.017) > KNO3--N(0.416±0.044) > K NH4+ -N (0.275±0.014) > KTN (0.258±0.083). Through the calculation of energy saving and carbon emission reduction of the combined system, the annual carbon emission reduction reaches more than 388203.55 kgCO2e, which significantly improves the carbon emission reduction effect and obtains a good green effect.